Telemedicine-equipped android interface-based heart rate monitoring - Hanifah Rahmi Fajrin; Bayu Satrio Adi; Heri Purwoko; Irma Permata Sari (Institute of Advanced Engineering and Science, 2021)
This research aimed to design a device that can monitor heart rate and help nurses or doctors when they need to monitor and retrieve data of patients. By utilizing Android as a displayer makes it easier for nurses to minimize data retrieval time. The principle of the tool is to record the heart rate data received by the ear clip sensor to be processed by the Atmega328 microcontroller, then displayed on the oled LCD and sent to Android phones via HC-05 Bluetooth for display. If the heart rate data is beyond the normal range, the Android application will post a notification in the form of an SMS to the recipient's cellphone. In testing the tool, it uses a comparison device (pulse oximetry) to determine its accuracy. Based on the testing, the heart rate monitoring device had a small error value of 0.32% and had the most substantial error value of 0.81%. The application of the monitoring system in android data can be sent well at a maximum distance of 13 meters, as well as the implementation of telemedicine in the form of a warning (SMS) can work properly.